The complete mitochondrial genome of the Placidochromis longimanus. (4th May 2017) - Xiong, Ye; Qin, Yuxia; Liu, Liyun; Liu, Jing; Jiang, Jie; Liu, Pei; Zhang, Lian-Qin; Qi, Dashi; Li, Zongyun
Abstract: The Placidochromis longimanus ( P. longimanus ), one species of Cichlidae, resides in the Lake Malawi in East Africa. In present study, for the first time, we reported the complete mitochondrial genome of P. longimanus, which has 16 581 bp in length, including 13 protein-coding genes, 2 ribosomal RNA, 22 transfer RNA genes, and 1 control zone. Moreover, its GC content is 45.99% (27.44% A, 26.58% T, 30.11% C, and 15.87% G), similar to that of Astatotilapia calliptera (the GC content of 45.90%). We further made the phylogenetic tree on the complete mitochondrial genomes of the above two species and other 11 closely related species to show their phylogenic relationship. The above results would facilitate our understanding of the evolution of Cichlidae mitochondrial genome.